Development of icon-based ATM menu interface / Sharifah Zaffy Safarina Syed Mubarat - Syed Mubarat, Sharifah Zaffy Safarina (2007)
This research looks at the icon represent towards ATM's menu interface that can be used by functional illiterate user to use ATM. Icon-based ATM interface can provide convenience to user who is functional illiterate so that they can easily interact with ATM in order to help them in making their transaction. The icon was found in the internet and been modified and redesigned it so that easier for user to understand. The 20 people are asked about the designed icons by using theory of affordance in order to examine whether they understand and satisfied to use the icon in ATM menu interface. If the designed are not understand by the participants, the icon is redesigned until meet the understandable icon. From the survey, 14 from the participants understood what the icons represent about. Most of them satisfied with the icon to be used in ATM's interface to replace the text-based interface. From this study, the icon that have been identify can be used by ATM designer as the alternative to replace the text-based ATM interface. These icons can give an idea to them in order to enhance the quality of services to meet customer expectations in services. A recommendation for future work is to add voice recognition in the ATM interface to ease the user for more valuable interaction. For ATM side, it is recommended providing the head phone so that the user can use the ATM more safely. Besides that, the icon-based ATM interface can be add more animation in the interface so that easier to user to understand. By using an animation, the user interface is more interactively.